Uji Aktivitas Hepatoprotektor Ekstrak Etanol Daun Rambutan (Nephelium lappaceum L.) pada Mencit Putih Jantan yang Diinduksi Parasetamol - Yuliawati Yuliawati; Waode Cahaya Widya Putri; Havizur Rahman (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Hepatotoxicity is a drug complication that is often found in long-term drug use because of the role of the liver in metabolizing drugs. Paracetamol is an analgesic and antipyretic drug that is often used by the community and is a safe choice when taken according to the dose. However, if consumed in excess and in the long-term  it causes hepatotoxicity (liver damage). Liver damage can be prevented by giving antioxidant compounds. Rambutan’s leaves contain secondary metabolites of alkaloids, tannins and saponins which are known to have antioxidant potential. The aim of the research is to determine the hepatoprotective activity and the effective dose of Rambutan leaves ethanol extract in male mice induced by patacetamol. The research method was The Randomize Posttest-only Control Group Design using 25 white mice which were divided into 5 groups. The results showed that there was a significant difference in the treatment group of rambutans leaf ethanol extract with the negative control group and a non-significant with the positive control group. Giving  extract doses of 100 mg/kg BW, 200 mg/kg BW and 400 mg/kg BW because it prevents the increase in levels of SGPT, SGOT, relative liver weight and reduces the percentage of damage to the hepatocytes of mice. The effective dose of rambutan’s leaf ethanol extract as a hepatoprotector is 400 mg/kg BW.